Welcome to Westonci.ca, where curiosity meets expertise. Ask any question and receive fast, accurate answers from our knowledgeable community. Explore our Q&A platform to find in-depth answers from a wide range of experts in different fields. Connect with a community of professionals ready to provide precise solutions to your questions quickly and accurately.
Sagot :
To determine which equation represents a line that passes through [tex]\(\left(4, \frac{1}{3}\right)\)[/tex] with a slope of [tex]\(\frac{3}{4}\)[/tex], we can use the point-slope form of a linear equation. The point-slope form is given by:
[tex]\[ y - y_1 = m(x - x_1) \][/tex]
where [tex]\((x_1, y_1)\)[/tex] is a point on the line and [tex]\(m\)[/tex] is the slope.
Given:
- Point [tex]\(\left(4, \frac{1}{3}\right)\)[/tex] implies [tex]\(x_1 = 4\)[/tex] and [tex]\(y_1 = \frac{1}{3}\)[/tex].
- Slope [tex]\(m = \frac{3}{4}\)[/tex].
Substitute these values into the point-slope form:
[tex]\[ y - \frac{1}{3} = \frac{3}{4}(x - 4) \][/tex]
Now let's compare this equation with the given options:
1. [tex]\(y - \frac{3}{4} = \frac{1}{3}(x - 4)\)[/tex]
2. [tex]\(y - \frac{1}{3} = \frac{3}{4}(x - 4)\)[/tex]
3. [tex]\(y - \frac{1}{3} = 4\left(x - \frac{3}{4}\right)\)[/tex]
4. [tex]\(y - 4 = \frac{3}{4}\left(x - \frac{1}{3}\right)\)[/tex]
The only option that matches our derived equation [tex]\(y - \frac{1}{3} = \frac{3}{4}(x - 4)\)[/tex] is the second option.
Therefore, the correct equation is:
[tex]\[ y - \frac{1}{3} = \frac{3}{4}(x - 4) \][/tex]
Hence, the correct option is [tex]\( \boxed{2} \)[/tex].
[tex]\[ y - y_1 = m(x - x_1) \][/tex]
where [tex]\((x_1, y_1)\)[/tex] is a point on the line and [tex]\(m\)[/tex] is the slope.
Given:
- Point [tex]\(\left(4, \frac{1}{3}\right)\)[/tex] implies [tex]\(x_1 = 4\)[/tex] and [tex]\(y_1 = \frac{1}{3}\)[/tex].
- Slope [tex]\(m = \frac{3}{4}\)[/tex].
Substitute these values into the point-slope form:
[tex]\[ y - \frac{1}{3} = \frac{3}{4}(x - 4) \][/tex]
Now let's compare this equation with the given options:
1. [tex]\(y - \frac{3}{4} = \frac{1}{3}(x - 4)\)[/tex]
2. [tex]\(y - \frac{1}{3} = \frac{3}{4}(x - 4)\)[/tex]
3. [tex]\(y - \frac{1}{3} = 4\left(x - \frac{3}{4}\right)\)[/tex]
4. [tex]\(y - 4 = \frac{3}{4}\left(x - \frac{1}{3}\right)\)[/tex]
The only option that matches our derived equation [tex]\(y - \frac{1}{3} = \frac{3}{4}(x - 4)\)[/tex] is the second option.
Therefore, the correct equation is:
[tex]\[ y - \frac{1}{3} = \frac{3}{4}(x - 4) \][/tex]
Hence, the correct option is [tex]\( \boxed{2} \)[/tex].
Thank you for your visit. We are dedicated to helping you find the information you need, whenever you need it. Thank you for your visit. We're dedicated to helping you find the information you need, whenever you need it. Keep exploring Westonci.ca for more insightful answers to your questions. We're here to help.